O fazer saber das danças afro: investigando matrizes negras em movimento - Ferraz, Fernando Marques Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In this research, the aim is to examine how choreographers and creators identified with the language of African dance engender the knowledge of this art in their practice. I reflect how this style enroll in the history of Brazilian dance through multiple artistic lineages and the reconstruction of the personal trajectories. Here I compare the different perspectives of their creators seen as partners in building a critical knowledge about the African dance and also analyze the tensions between their artistic formation (training), social identities and positions in the theatrical production field. I also discuss the negotiations over the political engagement of artists, their links with religious traditions, the debate with contemporary theatrical production and tensions between institutional spaces where they perform in order to review stereotypes and identify mediations responsible for a dynamical building of its repertoires and particularities

Nesta pesquisa, analisa-se como coreógrafos e intérprete-criadores identificados com a linguagem da dança afro engendram os saberes dessa arte em suas práticas. Busca-se refletir como esse estilo se inscreve na história da dança brasileira por meio da indicação de linhagens artísticas e da reconstrução das trajetórias de seus personagens. Para tanto, compara-se as diversas perspectivas de seus criadores, vistos como interlocutores na construção de um conhecimento crítico sobre a dança afro. São abordadas as tensões entre suas formações artísticas, identidades sociais e posicionamentos no campo da produção cênica. Também procurou-se refletir sobre as negociações em torno dos engajamentos políticos dos artistas, seus vínculos com as tradições religiosas, o debate com a produção cênica contemporânea e as tensões entre os espaços institucionais onde as performances se realizam com intuito de rever estereótipos e identificar mediações responsáveis pela construção dinâmica de seus repertórios e particularidades
Keywords: Dança - História; Dança - Brasil; Coreografos; Negros; Dance - History; Dance - Brazil; Blacks; Choreographers